2014
DOI: 10.21101/cejph.a3813
|View full text |Cite
|
Sign up to set email alerts
|

Obesity and Diet Awareness among Polish Children and Adolescents in Small Towns and Villages

Abstract: Awareness of healthy lifestyle behaviour is not sufficient to maintain optimal body mass. Knowledge about proper eating habits is better among girls than among boys, especially in the older age groups. However, in older groups, there was less physical activity due to spending more time in front of TV or the computer. High percentage of obese/overweight children and insufficient knowledge of nutrition may consequently result in increased risk of cardio-vascular diseases in adult population.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
17
0
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(25 citation statements)
references
References 15 publications
6
17
0
2
Order By: Relevance
“…This corroborates the findings of previous studies reporting females as being more health-conscious and followers of dietary recommendations than males [46,49,58,59]. In a study investigating dietary patterns among a national sample of Lebanese adults, females adhered more to the prudent pattern while males were found to mainly follow the western pattern [46].…”
Section: Discussionsupporting
confidence: 90%
“…This corroborates the findings of previous studies reporting females as being more health-conscious and followers of dietary recommendations than males [46,49,58,59]. In a study investigating dietary patterns among a national sample of Lebanese adults, females adhered more to the prudent pattern while males were found to mainly follow the western pattern [46].…”
Section: Discussionsupporting
confidence: 90%
“…respectively. They also reported that girls had a higher level of consciousness compared to boys, but that being conscious and aware was not sufficient to maintain optimal body mass (Stankiewicz et al, 2014). In Obafemi Awolowo University communities, the study carried out to measure the awareness of obesity among 236 female subjects aged 25-59 years 76.7% of women had low awareness about obesity awareness and health damage, and it was found that the level of education decreased and the awareness decreased (Ojofeitimi et al, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…Within the last decade, screen time behaviours such as excessive computer, tablet and smartphone use in adolescents, who have dealt with rapid technological developments, have contributed to the large amount of time that adolescents spend in an inactive way, preferring sedentary behaviour (1)(2)(3)(4). Current studies point out that sedentary activities are relatively independent of physical activity, i.e.…”
Section: Introductionmentioning
confidence: 99%